Matrix representation of real and hypercomplex Appell polynomials - Tomaz, Graça (2015)
In a unfied approach to the matrix representation of di erent types of real Appell polynomials was developed, based on a special matrix which has only the natural numbers as entries. This matrix, also called creation matrix, generates the Pascal matrix and allows to consider a set of Appell polynomials as solution of a rst order vector di erential equation with certain initial conditions. Besides a new elementary construction of the monogenic exponential function studied in, we analogously derive examples of di erent sets of non-homogenous hypercomplex Appell polynomials given by its matrix representation.